Beauty work: consumption, gender and hope in Yaounde, Cameroon - Majczak, E (2021)
Against the backdrop of trade and media liberalisation following the end of the Cold War, this dissertation examines visual self-fashioning among young Bamileke women struggling to attain social adulthood in Yaoundé, Cameroon. It asks why young women living in precarious conditions invest in beauty, dress and photographs of themselves to the extent they do. In order to answer this question, the thesis, moves beyond semiotic understandings of consumption and analyses self-fashioning in embodied and material terms. From this perspective, investments in beauty, dress and photographs not only index dreams and imaginations, but emerge as a set of skills and embodied knowledge that I propose to call “beauty work”. Each chapter examines different skills and collectively illustrate how, through their investments, young women can alter their social positions and create upward paths of social mobility. Thus, for young women beauty, dress and photographs became means by which to fashion and refashion social adulthood in a social, economic and political context where other paths—as employment and education—are compromised.